Labor relations, Catholic Church and rights in the sugarcane zone of Pernambuco: organization and mobilization of rural workers in the military regime - Andrade Teixeira Raposo, Cristhiane Laysa (Revista Crítica Histórica, 2019)
This paper aims at discussing the relationship between mobilizations of rural workers and the Catholic Church in the sugarcane zone of Pernambuco. The period covered spans from the beginning of the Church's interest in the rural areas relations, with the institutional renewal promoted by the Second Vatican Council and the Medellin Conference, to the repression of the institution by the military regime with the monitoring and persecution of members of the Church in defense of justice, dignity and rights of civil society, especially of the workers in Brazil. In order to carry out this analysis, we begin from the historiographical discussion and the crossing of sources provided by the Church, by means of communication and by the Information Services of the 1964 authoritarian regime.